ICT in Teaching Foreign Language in a Ukrainian University - Mykhailo Podoliak (Vasyl Stefanyk Precarpathian National University, 2024)
Modern technologies play such an essential role in human life that it is impossible to imagine a full-fledged existence without them. Their application is possible in almost any field of economy, improving human's life and increasing the efficiency of work. Technologies in education give students and teachers access to a much more considerable amount of information and opportunities compared to learning without technology. Today a student can learn a foreign language directly by hearing it not only in a video or audio recording, but also with the help of various applications, communicating with native speakers, learning their culture. Many scholars have been researching the role of ICT in language learning and have proved its effectiveness. The aim of the article is to determine the role of ICT in foreign language learning at Ukrainian Universities. In addition, we conducted a questionnaire of the English language teachers to determine the frequency of ICT usage at lectures. The results of the researched proved the hypothesis, set in the research, that the younger the teachers, the more often and diversely they use modern technologies in the educational process. Using ICT in teaching foreign languages requires not only the will and time of the teacher but also the skills and abilities to use modern technologies and Internet resources. The introduction of ICT in the educational process will have a positive effect on the results of student learning, among which we will highlight student interest in the educational process, modern and practical materials, immersion of students in the language and cultural environment, the opportunity to better study and master the academic material, communicate with native speakers.